Pseudoaneurysm of the internal maxillary artery secondary to subcondylar fracture: case report and literature review. Issue 4 (24th April 2018) - Moro, Alessandro; Todaro, Mattia; Pedicelli, Alessandro; Alexandre, Andrea; Pelo, Sandro; Doneddu, Piero; Gasparini, Giulio; Garagiola, Umberto; D'Amato, Giuseppe; Saponaro, Gianmarco
Abstract: Pseudoaneurysms are an uncommon complication of mandibular condylar-subcondylar fractures; however, if present, their recognition and management is mandatory to avoid life-threatening situations. The authors report a case of internal maxillary artery pseudoaneurysm rupture that occurred after an open reduction and internal fixation of a mandibular subcondylar fracture, along with a review of the literature.